2018
DOI: 10.33549/physiolres.933752
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Effect of Long-Term Microwave Radiation on Postnatal Neurogenesis in Rats: Morphological and Behavioral Study

Abstract: Processes of adult neurogenesis can be influenced by environmental factors. Here, we investigated the effect of microwave radiation (MWR) on proliferation and cell dying in the rat rostral migratory stream (RMS) -a migration route for the neuroblasts of the subventricular zone. Adult and juvenile (two weeks old) rats were exposed to a pulsed-wave MWR at the frequency of 2.45 GHz for 1 or 3 h daily during 3 weeks. Adult rats were divided into two groups: without survival and with two weeks survival after irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Comprehensive meta-analysis confirmed that RF-EMF predominantly influence the growth of human and faster-growing cells (45% and 47% of the included studies, respectively), and the observed effects are cell type- and dose-dependent under in vitro [ 130 ] and in vivo [ 131 , 132 , 133 ] conditions. However, in HCT-116 and DLD1 cells, RF-EMF from 900–2100 MHz applied up to 4 h did not induce changes in proliferation, as assessed by the MTT test [ 134 ]. These results are in line with our study, as we also did not observe a significant effect of RF-EMF on cell proliferation when miR-34a was not administered.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive meta-analysis confirmed that RF-EMF predominantly influence the growth of human and faster-growing cells (45% and 47% of the included studies, respectively), and the observed effects are cell type- and dose-dependent under in vitro [ 130 ] and in vivo [ 131 , 132 , 133 ] conditions. However, in HCT-116 and DLD1 cells, RF-EMF from 900–2100 MHz applied up to 4 h did not induce changes in proliferation, as assessed by the MTT test [ 134 ]. These results are in line with our study, as we also did not observe a significant effect of RF-EMF on cell proliferation when miR-34a was not administered.…”
Section: Discussionmentioning
confidence: 99%